Long-term efficacy and safety of drug-coated balloons versus drug-eluting stents for small coronary artery disease (BASKET-SMALL 2): 3-year follow-up of a randomised, non-inferiority trial. Issue 10261 (7th November 2020) - Jeger, Raban V; Farah, Ahmed; Ohlow, Marc-Alexander; Mangner, Norman; Möbius-Winkler, Sven; Weilenmann, Daniel; Wöhrle, Jochen; Stachel, Georg; Markovic, Sinisa; Leibundgut, Gregor; Rickenbacher, Peter; Osswald, Stefan; et al.
Summary: Background: In the treatment of de-novo coronary small vessel disease, drug-coated balloons (DCBs) are non-inferior to drug-eluting stents (DESs) regarding clinical outcome up to 12 months, but data beyond 1 year is sparse. We aimed to test the long-term efficacy and safety of DCBs regarding clinical endpoints in an all-comer population undergoing percutaneous coronary intervention. Methods: In this prespecified long-term follow-up of a multicentre, randomised, open-label, non-inferiority trial, patients from 14 clinical sites in Germany, Switzerland, and Austria with de-novo lesions in coronary vessels <3 mm and an indication for percutaneous coronary intervention were randomly assigned 1:1 to DCB or second-generation DES and followed over 3 years for major adverse cardiac events (ie, cardiac death, non-fatal myocardial infarction, and target-vessel revascularisation [TVR]), all-cause death, probable or definite stent thrombosis, and major bleeding (Bleeding Academic Research Consortium bleeding type 3–5). Analyses were performed on the full analysis set according to the modified intention-to-treat principle. Dual antiplatelet therapy was recommended for 1 month after DCB and 6 months after DES with stable symptoms, but 12 months with acute coronary syndromes. The study is registered with ClinicalTrials.gov, NCT01574534 and is ongoing. Findings: Between April 10, 2012, and Feb 1, 2017, of 883 patients assessed, 758 (86%) patients were randomly assigned to the DCB group (n=382) or the DES group (n=376). The Kaplan-Meier estimate of the rate of major adverse cardiac events was 15% in both the DCB and DES groups (hazard ratio [HR] 0·99, 95% CI 0·68–1·45; p=0·95). The two groups were also very similar concerning the single components of adverse cardiac events: cardiac death (Kaplan-Meier estimate 5% vs 4%, HR 1·29, 95% CI 0·63–2·66; p=0·49), non-fatal myocardial infarction (both Kaplan-Meier estimate 6%, HR 0·82, 95% CI 0·45–1·51; p=0·52), and TVR (both Kaplan-Meier estimate 9%, HR 0·95, 95% CI 0·58–1·56; p=0·83). Rates of all-cause death were very similar in DCB versus DES patients (both Kaplan-Meier estimate 8%, HR 1·05, 95% CI 0·62–1·77; p=0·87). Rates of probable or definite stent thrombosis (Kaplan-Meier estimate 1% vs 2%; HR 0·33, 95% CI 0·07–1·64; p=0·18) and major bleeding (Kaplan-Meier estimate 2% vs 4%, HR 0·43, 95% CI 0·17–1·13; p=0·088) were numerically lower in DCB versus DES, however without reaching significance. Interpretation: There is maintained efficacy and safety of DCB versus DES in the treatment of de-novo coronary small vessel disease up to 3 years. Funding: Swiss National Science Foundation, Basel Cardiovascular Research Foundation, and B Braun Medical.